2020
DOI: 10.1016/j.breast.2019.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine and musculoskeletal pain in the first year of adjuvant aromatase inhibitor treatment in early breast cancer patients

Abstract: a b s t r a c tBackground: Patients with breast cancer (BC) show strong interest in complementary and alternative medicine (CAM), particularly for adverse effects of adjuvant endocrine treatment d e.g., with letrozole. Letrozole often induces myalgia/limb pain and arthralgia, with potential noncompliance and treatment termination. This analysis investigated whether CAM before aromatase inhibitor (AI) therapy is associated with pain development and the intensity of AI-induced musculoskeletal syndrome (AIMSS) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…With regard to other medical specialties that make use of integrative medicine, a great search for complementary techniques occurs on the part of obese patients. These data corroborate other studies, which report findings on the limitations of conventional (CARLSON, et al, 2017); (LOPEZ, et al, 2018); (MILBURY, et al, 2020); (DENG, et al, 2018); (YOON, et al, 2019); (GARCIA, et al, 2021); (LU, et al, 2016); (SUN, MAO, LIU, YANG, & HE, 2020); (SHAO, et al, 2021); (WANG, YANG, FAN, & PEI, 2021); (McQUADE, et al, 2017); (LIMA, et al, 2021); (HACK, et al, 2020).…”
Section: Analysis and Discussionsupporting
confidence: 89%
“…With regard to other medical specialties that make use of integrative medicine, a great search for complementary techniques occurs on the part of obese patients. These data corroborate other studies, which report findings on the limitations of conventional (CARLSON, et al, 2017); (LOPEZ, et al, 2018); (MILBURY, et al, 2020); (DENG, et al, 2018); (YOON, et al, 2019); (GARCIA, et al, 2021); (LU, et al, 2016); (SUN, MAO, LIU, YANG, & HE, 2020); (SHAO, et al, 2021); (WANG, YANG, FAN, & PEI, 2021); (McQUADE, et al, 2017); (LIMA, et al, 2021); (HACK, et al, 2020).…”
Section: Analysis and Discussionsupporting
confidence: 89%
“…Cancer treatment typically includes surgery, chemotherapy and/or radiotherapy, and more recently immunotherapy [5][6][7]. Despite major improvements over the years in cancer therapy and early diagnosis, cancer patients still opt for complementary treatment to reduce the pain associated with conventional therapies and to increase their quality of life [8,9]. It has been reported that more than 50% of cancer patients use complementary treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported significant improvement in pain with massaging topical oil onto affected joints [ 62 ]. However, a study that looked at the effect of all CAM treatments, not a particular treatment, did not find any difference in pain between the control and CAM groups [ 65 ].…”
Section: Resultsmentioning
confidence: 99%